Ultrahigh-temperature metamorphic rocks from Howard Hills in the Napier Complex, East Antarctica - Yoshimura, Yasutaka; Motoyoshi, Yoichi; Grew, Edward S.; Miyamoto, Tomoharu; Carson, Christopher J.; Dunkley, Daniel J. (National Institute of Polar Research, 2000)
P(論文) The Howard Hills area consists predominantly of garnet felsic gneiss, orthopyroxene felsic gneiss and aluminous gneiss which contain garnet, sapphirine and sillimanite in various amounts The characteristic assemblage of sapphirine+quartz is present in quartzo-feldspathic layers within the aluminous gneiss The peak metamorphic conditions are estimated to have been about 1150- 1200℃ The condition is obtained by plotting the inferred original compositions of mesoperthites from the garnet felsic gneiss, orthopyroxene felsic gneiss, and aluminous gneiss on an An-Ab-Or ternary diagram, the original composition of the mesoperthites is derived by multiplying the modal ratio of host and lamella by their respective chemical compositions Probable P-T conditions for retrograde metamorphism are estimated using garnet-orthopyroxene isopleths, and range from 830 to 950℃ and 5 to 9 5 kbar Quartz inclusions in the cores of garnets from silica-undersaturated layers within the aluminous gneiss indicate the medium in which the garnets crystallized under the silica-oversaturated condition This implies mass transfer within the aluminous gneiss, probably involving partial melting that also led to high Y concentrations in garnet cores, high An values for plagioclase, and high Ba contents in mesoperthites from the aluminous gneiss Partial melt from aluminous gneiss was generated during prograde metamorphism and segregated, the restite might have undergone continuous ultrahigh-temperature metamorphism departmental bulletin paper